Kebiasaan Belajar Siswa Berprestasi melalui Pemanfaatan Jam Belajar Efektif di SMA Negeri 1 Keruak - Muhammad Habib Ash shiddiqi; Sulistia Safitri (Palapa: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2023)
The aim of the study was to find out the study habits of high achieving students in utilizing effective study hours at Keruak 1 Public High School. This research is a qualitative research with a case study approach. Teachers and outstanding students in class X MIPA I, X MIPA IV and X MIPA V SMA Negeri 1 Keruak as subjects in this study. To obtain data used observation (observation of objects), interviews to obtain detailed and in-depth information on objects, and documentation. then the data is processed using the Miles & Huberman model which then checks the correctness of the data using data triangulation. The research results obtained show the effective study hours habits of outstanding students at SMA Negeri 1 Keruak. Students are more likely to enjoy studying in the first hour of class than learning at the end of the lesson, students learn independently by searching for study material on the internet, textbooks and other learning resources, students always record and repeat material provided by the teacher. Suggestions for educators pay attention to the efficient use of student learning time and provide methods for time management. Parents must also provide support and facilities for efficient study time at home.